2020
DOI: 10.5334/gh.402
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Emergency Care for Possible Acute Coronary Syndrome Among Patients with Chest Pain or Shortness of Breath at a Tanzanian Referral Hospital

Abstract: Background: Acute coronary syndrome (ACS) is thought to be a rare diagnosis in sub-Saharan Africa, but little is known about diagnostic practices for patients with possible ACS symptoms in the region. Objective: To describe current care practices for patients with ACS symptoms in Tanzania to identify factors that may contribute to ACS under-detection. Methods: Emergency department patients with chest pain or shortness of breath at a Tanzanian referral hospital were prospectively observed. Medical histories wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
4
21
0
Order By: Relevance
“…HF was diagnosed in 26% of patients presenting to the ED with shortness of breath or chest pain, consistent with previous work finding HF to be a leading diagnosis among ED patients with these symptoms in SSA [ 5 , 6 , 28 ]. Importantly, only half the ED patients diagnosed with HF in Tanzania had a known prior diagnosis of HF, whereas the vast majority of HF patients presenting to EDs in high-income settings have a known prior history of HF [ 29 – 31 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…HF was diagnosed in 26% of patients presenting to the ED with shortness of breath or chest pain, consistent with previous work finding HF to be a leading diagnosis among ED patients with these symptoms in SSA [ 5 , 6 , 28 ]. Importantly, only half the ED patients diagnosed with HF in Tanzania had a known prior diagnosis of HF, whereas the vast majority of HF patients presenting to EDs in high-income settings have a known prior history of HF [ 29 – 31 ].…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, thirty-day outcomes following hospital presentation were poor, with a quarter of HF diagnosis patients dying within 30 days of ED diagnosis and few surviving patients using evidence-based therapies. HF was diagnosed in 26% of patients presenting to the ED with shortness of breath or chest pain, consistent with previous work finding HF to be a leading diagnosis among ED patients with these symptoms in SSA [5,6,28]. Importantly, only half the ED patients diagnosed with HF in Tanzania had a known prior diagnosis of HF, whereas the vast majority of HF patients presenting to EDs in high-income settings have a known prior history of HF [29][30][31].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Significant differences in prevalence across studies included reflect disparities in the diagnostic criteria and tools available between SSA countries and the population’s level of knowledge about the symptoms of coronary disease, which can lead to the underdiagnosis of ACS. 41 The limited availability of diagnostic tools (notably troponins) reported in several studies, including those by Kolo et al 33 and Hertz et al in Tanzania, 42 may also explain the low rate of documented MI cases (notably NSTEMI). The widespread use of troponin testing, as in developed countries, allows a greater screening of infarction cases, particularly NSTEMI.…”
Section: Discussionmentioning
confidence: 99%
“…Few published studies have used clustering methodology similar to ours to analyze the evolution of CVRFs. Several studies have analyzed the trajectories of one [ 18 , 19 , 20 , 21 ] or several [ 22 , 23 ] CVRFs using a variety of different methods, and have attempted to identify correlations between their findings and other factors or diseases. One such study [ 19 ] analyzed the evolution of SBP, for which 4 distinct trajectories were identified over time.…”
Section: Discussionmentioning
confidence: 99%